The Members of the Highly Diverse Crassostrea gigas Integrin Family Cooperate for the Generation of Various Immune Responses - Lv, Zhao; Qiu, Limei; Wang, Weilin; Liu, Zhaoqun; Liu, Qing; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2020)
The synergistic cooperation between multiple immune receptors greatly increases the diversity of immune responses generated in invertebrates. Studies on relevant receptor families might provide insights into characteristics specific to the innate immune system. Here, eight α- and three β-integrin subunits of the Crassostrea gigas spp. that were thought to form eight functional heterodimers were identified and studied. Oyster α/β subunits exhibited a higher degree of sequence and structural variability than those of members of the Homo sapiens and Drosophila melanogaster spp. Though α-subunits were evolutionally clustered with RGD and laminin receptors, they mainly formed an oyster-specific receptor branch, and lacked LDV-binding and PS3-type and αI-containing members, while β-subunits were clustered with insect βVs, and were distinct from those of the mollusc Biomphalaria glabrata. Although they lacked important branches, oyster integrins could bind to most ECM ligands, including RGDCPs, LDVCPs, GFOGERCPs, and laminins in a distinct binding pattern, and were distributed in different hemocyte subpopulations; this was indicative of their functional divisions in cellular immunity. Our experimental results showed that only specific subunits were selectively involved in hemocyte phagocytosis, migration, and encapsulation, and that some of them participated in more than one immune response in a sophisticated pattern. Notably, oyster β-subunits were probably arranged in the core, in order to mediate complex immune responses, unlike the arrangement in the human counterparts, which depended mainly on αI-containing members. This study represented the first comprehensive attempt to reveal the structural and evolutionary features of the integrin family and their involvement in cellular immune responses in the non-model invertebrate C. gigas, and sheds light on the characteristics specific to the innate immune system in the integrin family.